3D ultrasound evaluation of fetal ears in prenatal syndrome diagnosis – a comparative study - Roosen, Antonia Maria; Oelmeier, Kathrin; Möllers, Mareike; Willy, Daniela; Sondern, Kathleen Marie; Köster, Helen Ann; De Santis, Chiara; Eveslage, Maria; Schmitz, Ralf (Ultraschall in der Medizin - European Journal of Ultrasound, 2024)
Purpose The aim of the study was to assess fetal ears on prenatal 3D ultrasound and compare ear surface patterns and measurements between fetuses with syndromes and healthy fetuses.Materials and Methods Our study is based on 3D ultrasound images of 100 fetuses between the 20th and 37th week of gestation. We compared 50 ears of fetuses with syndromes (syndrome group) to 50 gestational age-matched ears of healthy fetuses (control group). The syndrome group consisted of fetuses with Trisomy 21 (n=13), Trisomy 18 (n=9) and other syndromes (n=28). The evaluation was based on measuring the ear length and width as well as developing categories to describe and compare different ear surface anomalies.Results Ears of fetuses with Trisomy 18 were on average 0.423 cm smaller in length (P<0.001) and 0.123 cm smaller in width (P=0.031) and grew on average 0.046 cm less in length per week of gestation (P=0.027) than those of healthy fetuses. Ears of fetuses with Trisomy 21 differed from healthy fetuses regarding the form of the helix (P=0.013) and the ratio of the concha to the auricle (P=0.037). Fetuses with syndromes demonstrated less ear surface details than their controls (syndrome group: P=0.018, P=0.005; other syndromes subgroup: P=0.020). We saw an increased richness of ear surface details at a later gestational age both in the fetuses with syndromes and the healthy fetuses.Conclusion Ears of fetuses with Trisomy 18 were smaller than their matched controls. Fetuses with syndromes varied in the evaluation of their ear surface from those of healthy fetuses. The ear surface can be analyzed with 3D ultrasound and might be useful as a screening parameter in syndrome diagnosis in the future.
Keywords: ear; 3D ultrasound; prenatal; syndrome; fetus